If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -10v + 9v + -9 + -1v = 0 Reorder the terms: 3 + -9 + -10v + 9v + -1v = 0 Combine like terms: 3 + -9 = -6 -6 + -10v + 9v + -1v = 0 Combine like terms: -10v + 9v = -1v -6 + -1v + -1v = 0 Combine like terms: -1v + -1v = -2v -6 + -2v = 0 Solving -6 + -2v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2v = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -2v = 0 + 6 -2v = 0 + 6 Combine like terms: 0 + 6 = 6 -2v = 6 Divide each side by '-2'. v = -3 Simplifying v = -3
| (6y-5)(3y+9)= | | f(x)=4+5x+e^5 | | 4.9x^2+24x=13 | | mn+m= | | 6x-24=x-5 | | 4.9x^2+24x-13=0 | | x=5+0.5x | | y=ln61(11/x) | | 2x+14=x-5 | | hbt=2pifort | | 8(t-2)+6t=7(2t+4)-9 | | -8u+5(u-5)=-4 | | 2=2(m-8)-5 | | 3p+2=11+2p | | 9(4x-3)=3(12x+9) | | -4+(2x^2)=x+7 | | 4+(2x^2)=x+7 | | y=-8-8 | | -4x-y=12 | | x-5y=16fory | | 13x-5=2x-71 | | 9(x+5)-(2x-3)=3 | | 129=2x^2-41x | | 1/5y-2/9=1/9y-6/5 | | -7.2x^2-33.1x+18.3=0 | | U/3-3.1=-7.9 | | 2x+6=3(9-x) | | -5=5/8n | | 14z=9z-5+4z | | 109+5x=119+4x | | 1/4y-3/7=1/7y-9/4 | | 15x-7=8x-56 |